Preferred and actual place of death in haematological malignancy. Issue 2 (8th July 2015) - Howell, D A; Wang, H I; Roman, E; Smith, A G; Patmore, R; Johnson, M J; Garry, A; Howard, M
Abstract : Objectives: Home is considered the preferred place of death for many, but patients with haematological malignancies (leukaemias, lymphomas and myeloma) die in hospital more often than those with other cancers and the reasons for this are not wholly understood. We examined preferred and actual place of death among people with these diseases. Methods: The study is embedded within an established population-based cohort of patients with haematological malignancies. All patients diagnosed at two of the largest hospitals in the study area between May 2005 and April 2008 with acute myeloid leukaemia, diffuse large B-cell lymphoma or myeloma, who died before May 2010 were included. Data were obtained from medical records and routine linkage to national death records. Results: 323 deceased patients were included. A total of 142 (44%) had discussed their preferred place of death; 45.8% wanted to die at home, 28.2% in hospital, 16.9% in a hospice, 5.6% in a nursing home and 3.5% were undecided; 63.4% of these died in their preferred place. Compared to patients with evidence of a discussion, those without were twice as likely to have died within a month of diagnosis (14.8% vs 29.8%). Overall, 240 patients died in hospital; those without a discussion were significantly more likely to die in hospital than those who had (p≤0.0001). Of those dying in hospital, 90% and 75.8% received haematology clinical input in the 30 and 7 days before death, respectively, and 40.8% died in haematology areas. Conclusions: Many patients discussed their preferred place of death, but a substantial proportion did not and hospital deaths were common in this latter group. There is scope to improve practice, particularly among those dying soon after diagnosis. We found evidence that some people opted to die in hospital; the extent to which this compares with other cancers is of interest.